2015
DOI: 10.1007/s12035-015-9246-7
|View full text |Cite
|
Sign up to set email alerts
|

Early Exposure to General Anesthesia Disrupts Spatial Organization of Presynaptic Vesicles in Nerve Terminals of the Developing Rat Subiculum

Abstract: Exposure to general anesthesia (GA) during critical stages of brain development induces widespread neuronal apoptosis and causes long-lasting behavioral deficits in numerous animal species. Although several studies have focused on the morphological fate of neurons dying acutely by GA-induced developmental neuroapoptosis, the effects of an early exposure to GA on the surviving synapses remain unclear. The aim of this study is to study whether exposure to GA disrupts the fine regulation of the dynamic spatial or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
(92 reference statements)
1
8
0
Order By: Relevance
“…Our study showed that exposure to anesthesia during a phase of intense synaptic development impairs mRNA and protein expression of Syn1 and Syt1, two presynaptic proteins that are critical for vesicle trafficking, docking and fusion. The results of this study are consistent with our previous ultrastructural observations of a shift in synaptic vesicle localization away from the presynaptic membrane, a reduction in the number of docked vesicles and increased inter-vesicular distance in the nerve terminals of young rats after neonatal anesthesia [8].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our study showed that exposure to anesthesia during a phase of intense synaptic development impairs mRNA and protein expression of Syn1 and Syt1, two presynaptic proteins that are critical for vesicle trafficking, docking and fusion. The results of this study are consistent with our previous ultrastructural observations of a shift in synaptic vesicle localization away from the presynaptic membrane, a reduction in the number of docked vesicles and increased inter-vesicular distance in the nerve terminals of young rats after neonatal anesthesia [8].…”
Section: Discussionsupporting
confidence: 93%
“…A previous study from our laboratory demonstrated a reduction in the number of vesicles docked at and within 100 nm from the presynaptic plasma membrane in the CA1-subiculum of anesthesia-treated rats five days after exposure [8]. Hence, the aims of this study were to investigate the effects of neonatal anesthesia on Syn 1 and Syt 1, two key regulators of synaptic vesicle trafficking, docking and fusion, and to test the link between changes in Syn 1 and Syt 1 and the learning and memory deficiencies observed after neonatal anesthesia.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…The discrepant reason may be due to their different drug regimen, which somehow decreased number of neurocytes, self-renewal and differentiation capacity of neural stem cells during the period of mature brains. On the one hand, it is acknowledged that the anesthetic mechanism of propofol in the developing CNS relates to multiple biological changes, including inhibition of network connections, inhibition of synaptic transmission efficiency and depression of neuronal activity [12]. On the other hand, the Schaffer collateral CA1 pathway is not the only pathway involved in LTP, thus there may be additional connections that could represent an alternative mechanism for long-term cognition alleviation.…”
Section: Discussionmentioning
confidence: 99%